Using cognition to predict the ability to understand medical treatment in brain and metastatic cancer. Issue 2 (12th November 2019) - Gerstenecker, Adam; Gammon, Meredith; Marotta, Dario; Fiveash, John; Nabors, Burt; Mulhauser, Kyler; Triebel, Kristen
Abstract: Objective: To determine if cognition can be used to identify persons with cancer at high risk for the impaired ability to understand treatment decisions. Methods: The association between understanding treatment decisions and cognition was examined using data from 181 participants across four groups: 67 with brain metastasis, 41 with metastatic cancer that has not spread to the brain, 27 with malignant glioma, and 46 healthy controls. All diagnoses were made by board‐certified oncologists and were verified histologically. Results: Results indicated that numerous cognitive functions were associated with the ability to understand treatment decisions in persons with cancer. The following proportion of participants demonstrated impaired understanding of treatment decisions in our three patient groups: approximately 51% malignant glioma, approximately 46% brain metastasis, and approximately 24% metastatic cancer. In a combined brain cancer group, we were able to use cognitive performance to predict the impaired ability to understand treatment decisions. Conclusions: An impaired ability to understand treatment decisions is prevalent in persons with brain cancer and persons with metastatic cancer. Performance on a brief cognitive battery can be used to help clinicians identify patients at particular risk for impaired medical decision making.